2008
DOI: 10.1016/j.jcrs.2008.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the anterior chamber angle after implantation of iris-fixated phakic intraocular lenses

Abstract: Partial localized narrowing of anterior chamber angles that occurred after pIOL implantation induced acute and chronic anterior chamber inflammation in patients with large angle alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…With 1‐year follow up, long‐term complications such as cataract formation and glaucoma risk cannot be fully assessed, and other studies have shown both cataract formation 16 and narrowing of the drainage angle after phakic IOL placement, 18 so it is especially important to continue slit‐lamp and IOP monitoring in these patients on a long‐term basis. Other studies have monitored endothelial cell count and found a degree of endothelial cell loss between 4% at 10 years postoperative and 9.5% at 4 years postoperative.…”
Section: Discussionmentioning
confidence: 99%
“…With 1‐year follow up, long‐term complications such as cataract formation and glaucoma risk cannot be fully assessed, and other studies have shown both cataract formation 16 and narrowing of the drainage angle after phakic IOL placement, 18 so it is especially important to continue slit‐lamp and IOP monitoring in these patients on a long‐term basis. Other studies have monitored endothelial cell count and found a degree of endothelial cell loss between 4% at 10 years postoperative and 9.5% at 4 years postoperative.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] It would be valuable to know whether the corneal power measurements that it provides are reliable for IOL power calculation. In the present study, the accuracy was good; Scheimpflug corneal Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Coullet et al 22 report that within 1 year of surgery, IOP did not significantly change after Artisan or Artiflex pIOL implantation. However, Yamaguchi et al 117 report that after implantation of an Artisan/Verisyse pIOL, partial narrowing of the anterior chamber angle of more than 5 degrees occurred in the area where the pIOL haptics pinched the iris. This did not affect IOP.…”
Section: Intraocular Pressure Elevationmentioning
confidence: 99%